Indocyanine Green (ICG) Fluorescent Cholangiography During Robotic Cholecystectomy: Results of 184 Consecutive Cases in a Single Institution. (December 2014) - Daskalaki, Despoina; Fernandes, Eduardo; Wang, Xiaoying; Bianco, Francesco Maria; Elli, Enrique Fernando; Ayloo, Subashini; Masrur, Mario; Milone, Luca; Giulianotti, Pier Cristoforo
Background/Aim. Laparoscopic cholecystectomy is currently the gold standard treatment for gallstone disease. Bile duct injury is a rare and severe complication of this procedure, with a reported incidence of 0.4% to 0.8% and is mostly a result of misperception and misinterpretation of the biliary anatomy. Robotic cholecystectomy has proven to be a safe and feasible approach. One of the latest innovations in minimally invasive technology is fluorescent imaging using indocyanine green (ICG). The aim of this study is to evaluate the efficacy of ICG and the Da Vinci Fluorescence Imaging Vision System in real-time visualization of the biliary anatomy. Methods. A total of 184 robotic cholecystectomies with ICG fluorescence cholangiography were performed between July 2011 and February 2013. All patients received a dose of 2.5 mg of ICG 45 minutes prior to the beginning of the surgical procedure. The procedures were multiport or single port depending on the case. Results. No conversions to open or laparoscopic surgery occurred in this series. The overall postoperative complication rate was 3.2%. No biliary injuries occurred. ICG fluorescence allowed visualization of at least 1 biliary structure in 99% of cases. The cystic duct, the common bile duct, and the common hepatic duct were successfully visualized with ICG in 97.8%, 96.1%, and 94% of cases, respectively. Conclusions. ICG fluorescent cholangiography during robotic cholecystectomy is a safe and effective procedure that helps real-time visualization of the biliary tree anatomy.